Skrining Penyakit Kardiovaskular pada Populasi Rentan Covid-19 di Jorong Bansa, Kabupaten Agam - Mulyanti Roberto Muliantino; Yuanita Ananda; Rika Sarfika (Warta Pengabdian Andalas, 2022)
Cardiovascular disease was a major degenerative disease with high morbidity and mortality rates. Patients with cardiovascular diseases such as hypertension, coronary heart disease and heart failure were vulnerable populations during the COVID-19 pandemic. They have high risk of worsening their condition when infected of the COVID-19 virus. Health screening was one of the efforts in preventive measure to identify this risk group. This activity aimed to identify people who are at risk or suffer from cardiovascular disease. The method using physical examination, including blood pressure, cholesterol levels and blood sugar levels. There were 22 people in Jorong Bansa carried out in this activity. The results of the screening found that there were 3 people with high blood pressure in the stage 1 hypertension and 3 people with the stage 2 hypertension. There were 6 people with cholesterol levels > 200 mg/dl and 1 person was identified as having a history of diabetes melitus with blood sugar levels > 200 mg/dl. Screening can be a preventive effort to identifying the disease and complication preventive. An educational programme was recommended to increase knowledge and self-management related to their illness.